Pengaruh Pengolahan dengan Microwave terhadap Kandungan Asam Lemak Omega-3 Filet Ikan Kembung - Laras Rianingsih; Siti Ari Budhiyanti; Nurfitri Ekantari (Universitas Gadjah Mada, 2006)
The effects of cooking by microwave oven on the moisture content, lipid content, iodine value, and omega-3 fatty acid composition of scad fish (Rastrelliger sp.) fillets were determined. The objective of the study was to find the effect of cooking by microwave oven in the fillet. The scad fish fillets were cooked by different power level and times. The moisture content, lipid content, iodine value, EPA and DHA of flesh were changed by cooking. Cooking by microwave oven decreased EPA and DHA composition. The decreasing of EPA are 6.53%, 15.97%, and 27,69%, respectively for 1/3 cooked, 2/3 cooked, and well cooked at high power level, and 31.21%; 46.37% and 75.91% at medium high power level. Meanwhile, the decresing of DHA were not significantly different compared to the control. Treatment of 1/3 cooked, 2/3 cooked, and well cooked at high power level resulting to the DHA reduction of 1.32 %, 7.52 %, and 9.63 %, respectively, whereas at medium high power level, DHA reduction were 8.09 %, 20.18 % and 23.32 % respectively. The decreasing of EPA and DHA were enhanced by a longer time of cooking. Cooking with high power lever was better than medium high power level.